2021
DOI: 10.5492/wjccm.v10.i3.47
|View full text |Cite
|
Sign up to set email alerts
|

Frequency of hepatic steatosis and its association with the pneumonia severity score on chest computed tomography in adult COVID-19 patients

Abstract: BACKGROUND Recent studies of the coronavirus disease 2019 (COVID-19) demonstrated that obesity is significantly associated with increased disease severity, clinical outcome, and mortality. The association between hepatic steatosis, which frequently accompanies obesity, and the pneumonia severity score (PSS) evaluated on computed tomography (CT), and the prevalence of steatosis in patients with COVID-19 remains to be elucidated. AIM To assess the frequency of hepatic ste… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
9
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 12 publications
(9 citation statements)
references
References 22 publications
0
9
0
Order By: Relevance
“… 36 showed that liver steatosis as assessed by CT (liver attenuation <40 HU) was more frequent in patients with COVID-19 infections compared with controls (40.9% vs. 19.4%, P < .001). 36 Palomar-Lever et al. 35 showed that liver steatosis (liver-to-spleen attenuation ratio ≤ 0.9) was more common in patients with severe COVID-19 infections compared with non-severe infections (69.9 vs 29%).…”
Section: Discussionmentioning
confidence: 92%
See 1 more Smart Citation
“… 36 showed that liver steatosis as assessed by CT (liver attenuation <40 HU) was more frequent in patients with COVID-19 infections compared with controls (40.9% vs. 19.4%, P < .001). 36 Palomar-Lever et al. 35 showed that liver steatosis (liver-to-spleen attenuation ratio ≤ 0.9) was more common in patients with severe COVID-19 infections compared with non-severe infections (69.9 vs 29%).…”
Section: Discussionmentioning
confidence: 92%
“…For example, Tahtabasi et al. 36 showed that liver steatosis as assessed by CT (liver attenuation <40 HU) was more frequent in patients with COVID-19 infections compared with controls (40.9% vs. 19.4%, P < .001). 36 Palomar-Lever et al.…”
Section: Discussionmentioning
confidence: 99%
“…The onset and severity of the disease may be related to several risk factors. It is claimed in the literature that control groups who were COVID-19-positive had a lower risk of HS than positive groups (7,11,23). Additionally, Palomar-Lever et al and Corapli et al discovered that CT-SS was greater in individuals with COVID-19 with HS.…”
Section: Discussionmentioning
confidence: 99%
“…3 a, b, c, d). This was considered to reflect the appearance of fatty change in the patient’s liver [ 15 ]. Consecutive SARS-CoV-2 PCR assays were conducted three times (on days 14, 15, and 17) and were all negative.…”
Section: Introductionmentioning
confidence: 99%